COMPARISON BETWEEN EFFICACY OF TYMPANOPLASTY WITH AND WITHOUT CORTICAL MASTOIDECTOMY IN TUBO-TYMPANIC OTITIS MEDIA IN ADULTS - Erum Shahzadi; Zia -us-Salam Qazi; Sarfraz Latif; Anees ur Rehman; Ikram Ullah; Tahir Haroon (Journal of Ayub Medical College Abbottabad, 2024)
Background: Chronic suppurative otitis media (CSOM) tubo-tympanic type is a common ear condition in underdeveloped nations. Cortical mastoidectomy in conjunction with tympanoplasty has long been regarded as the preferred surgical procedure for patients with chronic non-cholesteatomatous otitis media. Studies contrasting tympanoplasty with and without cortical mastoidectomy improved hearing, but the results were comparable. Both of these procedures are still debatable and mandate further research. This comparison has not been conducted in Pakistan before. Our objective is to evaluate whether tympanoplasty is effective in managing tubo-tympanic otitis media in patients with or without cortical mastoidectomy. Methods: Eighty-two patients (equally divided into two groups) were recruited from the Shaikh Zayed Hospital, Lahore. Group A (n=41) referred to tympanoplasty with mastoidectomy and group B (n=41) referred to tympanoplasty alone. Data was gathered using a pre-designed Proforma, and SPSS version 25.0 was used for analysis. Post-operative hearing improvement was calculated from the audiometric’ air-bone gap before the operation minus the ABG of post-operative follow-up at 16 weeks. A hearing gain of at least 15dB was considered clinically relevant. Results: Hearing improvement was observed in 73.3% of participants in group A while 83.3% in group B, grafting status was 95.1% in group B and 90.2% in group A, and discharge presence was 7.3% and 17% in group A and group B respectively. Conclusion: In CSOM, mastoidectomy does not add significant benefit in terms of hearing & graft uptake, however, it is advantageous if the middle ear mucosa is unhealthy. Tympanoplasty alone is sufficient if the middle ear mucosa is healthy